An Apology for Exegesis of 1 Thess 2,1-12 - Brookins, Timothy (Biblica, 2022)
The history of modern interpretation has vacillated between an 'apologetic' and a 'parenetic' reading of 1 Thess 2,1-12. The present article begins with a critical review of recent scholarship on this passage and determines that the crystallization of a two-view debate has had the infelicitous effect of (1) projecting greater divergence of opinion than is in fact present in the scholarly discussion, while (2) creating 'summary' readings of the passage that fail to reflect the critical work of close exegesis. In its main part, the article then offers a fresh and detailed exegesis of 1 Thess 2,1-12 within the context of chapters 1-3 and comes to determinations at many points that undermine key supports used in defense of 'apologetic' readings.